Developmental Expression of Violaxanthin De-Epoxidase in Leaves of Tobacco Growing under High and Low Light - Bugos, Robert C. (American Society of Plant Physiologists, 1999)
Violaxanthin de-epoxidase (VDE) is a lumen-localized enzyme that catalyzes the de-epoxidation of violaxanthin in the thylakoid membrane upon formation of a transthylakoid pH gradient. We investigated the developmental expression of VDE in leaves of mature tobacco (Nicotiana tabacum) plants grown under high-light conditions (in the field) and low-light conditions (in a growth chamber). The difference in light conditions was evident by the increased pool size (violaxanthin + antheraxanthin + zeaxanthin, VAZ) throughout leaf development in field-grown plants. VDE activity based on chlorophyll or leaf area was low in the youngest leaves, with the levels increasing with increasing leaf age in both high- and low-light-grown plants. However, in high-light-grown plants, the younger leaves in early leaf expansion showed a more rapid increase in VDE activity and maintained higher levels of VDE transcript in more leaves, indicating that high light may induce greater levels of VDE. VDE transcript levels decreased substantially in leaves of mid-leaf expansion, while the levels of enzyme continued to increase, suggesting that the VDE enzyme does not turn over rapidly. The level of VDE changed in an inverse, nonlinear relationship with respect to the VAZ pool, suggesting that enzyme levels could be indirectly regulated by the VAZ pool.